1971
DOI: 10.1139/v71-079
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and Spectral Studies on Cobalt(II) Fluorosulfate

Abstract: The magnetic moment of cobalt(I1) fluorosulfate has been measured over the temperature range 312 to 120 "K and the results agree with theory for cobalt(I1) in a regular octahedral ligand environment with h equal to the free-ion value and no reduction in the magnetic moment due to electron delocalization. From its electronic spectrum, values of the ligand-field parameters Dq and B are estimated to be 765 and 860 cm-', respectively. The infrared spectrum shows no distortion of the fluorosulfate groups from C3" s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
13
0

Year Published

1974
1974
2016
2016

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 8 publications
1
13
0
Order By: Relevance
“…Magnetic susceptibilities were determined at field strengths of approximately 4500 and 7000 G using the Guoy equipment and calibration procedure described previously (2). None of the samples gave evidence for dependence of magnetic susceptibilities on field strength.…”
Section: Physical Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Magnetic susceptibilities were determined at field strengths of approximately 4500 and 7000 G using the Guoy equipment and calibration procedure described previously (2). None of the samples gave evidence for dependence of magnetic susceptibilities on field strength.…”
Section: Physical Methodsmentioning
confidence: 99%
“…A structural model was proposed involving a layer type of structure in which each fluorosulfate group acts, via its'three oxygen atoms, as a bridge between three different metal ions (2). On the basis of vibrational and electronic spectral studies and magnetic susceptibility measurements Co(FSO,), was shown to have octahedral coordination of cobalt ions with a COO, skeleton not significantly distorted from 0, symmetry.…”
Section: Introductionmentioning
confidence: 99%
“…There have been a number of reports recently on the preparation and characterization of metal fluorosulfate compounds, including binary metal mono-(1,2), bis-(3-8), tris-(3,9, lo), and tetrakis-(10, I I ) fluorosulfates, chloro-and organotinfluorosulfates ( 1 [1][2][3][4][5][6][7][8][9][10][11][12][13][14], oxyfluorosulfates (1 5-17) and methylcyanide complexes of metal fluorosulfates (1 8). In most instances infrared spectra have been recorded and evidence regarding structure and bonding has been deduced from the number and energies of observed anion vibrations.…”
Section: Introductionmentioning
confidence: 99%
“…The infrared spectra of calcium, zinc, copper, tin, and cobalt bisfl~~orosulfates (3,7,8) have attempt to resolve such discrepancies in the literature and to extend the range of metal bisfluorosulfates studied, we have reexamined the spectra of a number of compounds and report for the first time the complete spectra (over the frequency range 250 to 1400 cm-') of the fluorosulfates of divalent magnesium, strontium, barium, cadmium, mercury, manganese, iron, nickel, and lead.…”
Section: Introductionmentioning
confidence: 99%
“…This means that the metal-anion coordination must involve terdentate fluorosulphate groups with ali three oxygen atoms coordinated in an equivalent manner. Thus the structure of Fe(SO,F), is presumably of the terdentate bridging type proposed for Co(SO,F), (6), and should involve a trigonal distortion of the Fe-0, octahedron. Fe(SO,F), therefore seemed an attractive compound to investigate, and this paper reports detailed measurements of its susceptibility and Mossbauer spectra over wide ranges of temperature.…”
Section: Inkrodlactionmentioning
confidence: 91%